Pemanfaatan Aplikasi Liveworksheet dalam Peningkatan Keaktifan Belajar Siswa pada Pembelajaran Matematika di Kelas VI Sekolah Dasar Negeri 060858 Medan Tembung - Hutagaol, Gian A. P.; Nasution, Ismail Saleh; Sidabungke, Sri Siswanti M (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study investigates the effectiveness of integrating Liveworksheet, a web-based digital platform, in enhancing elementary school students' interest and learning outcomes in mathematics. The research was motivated by the observed decline in students' engagement during mathematics lessons and the urgent need for innovative, technology-integrated teaching approaches. Employing a classroom action research design, the study was conducted in two cycles and utilized observation, interviews, and documentation for data collection. The findings revealed a marked improvement in both student interest and academic performance, as evidenced by increased scores and active participation during the learning process. The interactive nature of Liveworksheet enabled students to engage with content more meaningfully, thereby fostering motivation and deeper understanding. These results suggest that the use of Liveworksheet can serve as an effective pedagogical strategy for addressing learning disengagement in elementary education. The study concludes by recommending the broader adoption of web-based tools like Liveworksheet and encourages further development of creative digital learning media to enhance instructional effectiveness in primary education settings.